Circa expeditiones arduas. The Vicegerent's Office under the Durazzo Dynasty (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
The aim of this article is to analyse the position of the vicegerent, a peripheric office which spread in the Angevin kingdom of Naples since the second half of 14th century and became established during the period of the Durazzo dynasty (1381-1435). To achieve the goal, the article starts from the exposition and study of four different letters of appointment as vicegerent, already edited in the past, in order to understand the powers and duties of this officer and to place it in the institutional system of the Angevin kingdom. The paper attempts to understand the reasons which led the vicegerents, officers invested with extraordinary powers, to become an alternative to the justiciars at the top of the provinces of Southern Italy. Moreover, the first documentary evidences of the office in the late 1350s will be reconstructed, thus providing a first chronotaxis of the vicegerents in the Durazzo period, with a short analysis of the people who held the office. The paper seeks to give a contribution to the studies which examine the ‘extraordinary’ offices in the late Middle Ages.
Keywords: Vicegerents; justiciars; Anjou-Durazzo; kingdom of Naples; emergency powers; preambles